ISIS-4: a randomised factorial trial assessing early oral captopril, oral mononitrate, and intravenous magnesium sulphate in 58,050 patients with suspected acute myocardial infarction. ISIS-4 (Fourth International Study of Infarct Survival) Collaborative Group. - Collins, R; Peto, R; Flather, M; Parish, S; Sleight, P; Conway, M; Pipilis, A; Baigent, C; Barnett, D; Boissel, J; Budaj, A; Cairns, J; et al. (1995)
58,050 patients entering 1086 hospitals up to 24 h (median 8 h) after the onset of suspected acute myocardial infarction (MI) with no clear contraindications to the study treatments (in particular, no cardiogenic shock or persistent severe hypotension) were randomised in a "2 x 2 x 2 factorial" study. The treatment comparisons were: (i) 1 month of oral captopril (6.25 mg initial dose titrated up to 50 mg twice daily) versus matching placebo; (ii) 1 month of oral controlled-release mononitrate (30 mg initial dose titrated up to 60 mg once daily) versus matching placebo; and (iii) 24 h of intravenous magnesium sulphate (8 mmol initial bolus followed by 72 mmol) versus open control. There were no significant "interactions" between the effects of these three treatments, and the results for each are based on the randomised comparison of about 29,000 active versus 29,000 control allocated patients. Captopril There was a significant 7% (SD 3) proportional reduction in 5-week mortality (2088 [7.19%] captopril-allocated deaths vs 2231 [7.69%] placebo; 2p = 0.02), which corresponds to an absolute difference of 4.9 SD 2.2 fewer deaths per 1000 patients treated for 1 month. The absolute benefits appeared to be larger (perhaps about 10 fewer deaths per 1000) in certain higher-risk groups, such as those presenting with a history of previous MI or with heart failure. The survival advantage appeared to be maintained in the longer term (5.4 [SD 2.8] fewer deaths per 1000 at 12 months). Captopril was associated with an increase of 52 (SD 2) patients per 1000 in hypotension considered severe enough to require termination of study treatment, of 5 (SD 2) per 1000 in reported cardiogenic shock, and of 5 (SD 1) per 1000 in some degree of renal dysfunction. It produced no excess of deaths on days 0-1, even among patients with low blood pressure at entry. Mononitrate There was no significant reduction in 5-week mortality, either overall (2129 [7.34%] mononitrate-allocated deaths vs 2190 [7.54%] placebo) or in any subgroup examined (including those receiving short-term non-study intravenous or oral nitrates at entry). Further follow-up did not indicate any later survival advantage. The only significant side-effect of the mononitrate regimen studied was an increase of 15 (SD 2) per 1000 in hypotension. Those allocated active treatment had somewhat fewer deaths on days 0-1, which is reassuring a bout the safety of using nitrates early in acute MI.(ABSTRACT TRUNCATED AT 400 WORDS)